PERBEDAAN ASPEK KEBAHASAAN TERJEMAHAN SURAH AL-MULK VERSI KEMENTERIAN AGAMA REPUBLIK INDONESIA DAN VERSI MAHMUD JUNUS - Umi Kulsum Amalliyah (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2018)
This research is motivated presence in Indonesian translation differences between translations of the Quran version Ministry of Religious Affairs of Indonesia and the translation of the Koran version Prof. H. Mahmud Junus in surah Al-Mulk. The research problem involves the differences of diction, differences pronomina, spelling differences, and differences of the sentence contained in the translation of the Quran surah Al-Mulk of the Ministry of Religious Affairs of the Republic of Indonesia and Prof. H. Mahmud Junus. The purpose of this study describes a differences of diction, differences pronomina, spelling differences, and differences of the sentence contained in the translation of the Quran surah Al-Mulk of the Ministry of Religious Affairs of the Republic of Indonesia and Prof. H. Mahmud Junus. The theory used is the differences of diction, pronomina, spelling and sentence. The method used is descriptive qualitative interpretative The results showed that there are differences in diction, pronomina, spelling, and sentence among the Translation of Surah Al-Mulk version of the Ministry of Religious Affairs Republic of Indonesia with version Prof. H. Mahmud Junus.